2017
DOI: 10.1038/nm.4268
|View full text |Cite
|
Sign up to set email alerts
|

Antibody 10-1074 suppresses viremia in HIV-1-infected individuals

Abstract: Monoclonal antibody 10-1074 targets the V3 glycan supersite on the HIV-1 envelope protein. It is among the most potent anti-HIV-1 neutralizing antibodies isolated to date. Here we report on its safety and activity in 33 subjects who received a single intravenous infusion of the antibody. 10-1074 was well tolerated with a half-life of 24.0 days in uninfected and 12.8 days in HIV-1-infected subjects. 13 viremic subjects received the highest dose of 30 mg/kg 10-1074. 11 of these participants were 10-1074-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
507
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(548 citation statements)
references
References 66 publications
(114 reference statements)
19
507
0
7
Order By: Relevance
“…These strategies have enabled the isolation of many dozens of antibodies from elite neutralizers, and some of these have exceptional breadth (approaching 99% of circulating viruses) and potency in the picomolar range [44, 4648]. As well has providing insights into the host immune response, these remarkable antibodies are now increasingly being tested by passive immunization for either HIV prevention or treatment, with the likelihood of this being successful supported by extensive animal and preclinical human data [3840, 4952]. This approach will almost certainly require the use of combinations of bNAbs, both to maximize coverage and (in the context of treatment) to reduce viral escape [53].…”
Section: Broadly Neutralizing Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies have enabled the isolation of many dozens of antibodies from elite neutralizers, and some of these have exceptional breadth (approaching 99% of circulating viruses) and potency in the picomolar range [44, 4648]. As well has providing insights into the host immune response, these remarkable antibodies are now increasingly being tested by passive immunization for either HIV prevention or treatment, with the likelihood of this being successful supported by extensive animal and preclinical human data [3840, 4952]. This approach will almost certainly require the use of combinations of bNAbs, both to maximize coverage and (in the context of treatment) to reduce viral escape [53].…”
Section: Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…Of note, escape from passively administered bNAbs is not necessarily as slow as escape during infection. Indeed, in a recent clinical trial of the V3-glycan bNAb 10–1074, over 90% of viruses had escaped within four weeks of infusion [40]. Thus, the intrinsic “escapability” from bNAbs targetting conserved epitopes may also be impacted by a more dynamic interplay of viral fitness and escape in the context of polyclonal plasma [71, 97].…”
Section: Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…A cocktail of five antibodies has shown therapeutic potential in animal studies (Klein et al, 2012), and antibodies such as 3BNC117, VRC01, and members of the PGT121 family are showing promise in clinical studies (Bar et al, 2016; Caskey et al, 2015, 2017; Scheid et al, 2016; Schoofs et al, 2016). VRC01, a human antibody identified from an HIV-1-infected donor, is capable of neutralizing over 90% of HIV-1, with a median 50% inhibitory concentration (IC 50 ) of 0.33 µg/mL (Wu et al, 2010), and its preventive efficacy is currently being assessed in a Phase IIb prevention study, with dosing up to ~2 g VRC01 every 2 months for an average adult.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from human trials of passive administration of broadly neutralizing antibodies 2F5, 4E10, and 2G12 in combination (53)(54)(55) and monotherapy with CD4 binding site-specific antibodies VRC01 (12,16) and 3BNC117 (13,15) as well as the V3 glycanspecific 10-1074 (14) have been published. Each trial reported the emergence of viral resistance mutations to the active antibody.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, antibody based therapies may be superior to current highly active antiretroviral therapy (HAART) regimens in that along with viral suppression they may directly induce the clearance of infected cells by the above-mentioned mechanisms (11). Recently it was demonstrated that passive administration of the potent CD4 binding site-specific antibodies VRC01 (12) and 3BNC117 (13) as well as the V3-specific monoclonal antibody 10-1074 (14) was safe and when given to viremic HIV-infected individuals off treatment resulted in a 0.8-to 2.5-log 10 reduction in plasma viremia. Notably, administration to HIV-1-infected volunteers on suppressive HAART antibody therapy resulted in a delayed rebound of viremia following treatment interruption (15,16).…”
mentioning
confidence: 99%